Mechanochemical synthesis of poly(trimethylene carbonate)s: an example of rate acceleration - Park, Sora; Kim, Jeung Gon (Beilstein Journal of Organic Chemistry, 2019)
Mechanochemical polymerization is a rapidly growing area and a number of polymeric materials can now be obtained through green mechanochemical synthesis. In addition to the general merits of mechanochemistry, such as being solvent-free and resulting in high conversions, we herein explore rate acceleration under ball-milling conditions while the conventional solution-state synthesis suffer from low reactivity. The solvent-free mechanochemical polymerization of trimethylene carbonate using the organocatalysts 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) and 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) are examined herein. The polymerizations under ball-milling conditions exhibited significant rate enhancements compared to polymerizations in solution. A number of milling parameters were evaluated for the ball-milling polymerization. Temperature increases due to ball collisions and exothermic energy output did not affect the polymerization rate significantly and the initial mixing speed was important for chain-length control. Liquid-assisted grinding was applied for the synthesis of high molecular weight polymers, but it failed to protect the polymer chain from mechanical degradation.
Keywords: aliphatic polycarbonate; green polymerization; mechanochemistry; organocatalyst; poly(trimethylene carbonate)

(untitled) - James, S. L.; Friščić, T. (Chem. Soc. Rev., 2013)

(untitled) - James, S. L.; Adams, C. J.; Bolm, C.; Braga, D.; Collier, P.; Friščić, T.; Grepioni, F.; Harris, K. D. M.; Hyett, G.; Jones, W.; Krebs, A.; Mack, J.; et al. (Chem. Soc. Rev., 2012)

(untitled) - Hernández, J. G. (Beilstein J. Org. Chem., 2017)

(untitled) - Do, J.-L.; Friščić, T. (ACS Cent. Sci., 2017)

(untitled) - Howard, J. L.; Cao, Q.; Browne, D. L. (Chem. Sci., 2018)

(untitled) - Hernández, J. G.; Bolm, C. (J. Org. Chem., 2017)

(untitled) - Li, J.; Nagamani, C.; Moore, J. S. (Acc. Chem. Res., 2015)

(untitled) - Kean, Z. S.; Craig, S. L. (Polymer, 2012)

(untitled) - Chen, Z.; Mercer, J. A. M.; Zhu, X.; Romaniuk, J. A. H.; Pfattner, R.; Cegelski, L.; Martinez, T. J.; Burns, N. Z.; Xia, Y. (Science, 2017)

(untitled) - Ravnsbæk, J. B.; Swager, T. M. (ACS Macro Lett., 2014)

(untitled) - Grätz, S.; Borchardt, L. (RSC Adv., 2016)

(untitled) - Grätz, S.; Wolfrum, B.; Borchardt, L. (Green Chem., 2017)

(untitled) - Ohn, N.; Shin, J.; Kim, S. S.; Kim, J. G. (ChemSusChem, 2017)

(untitled) - Lee, G. S.; Moon, B. R.; Jeong, H.; Shin, J.; Kim, J. G. (Polym. Chem., 2019)

(untitled) - Ohn, N.; Kim, J. G. (ACS Macro Lett., 2018)

(untitled) - Malca, M. Y.; Ferko, P.-O.; Friščić, T.; Moores, A. (Beilstein J. Org. Chem., 2017)

(untitled) - Zhu, X.; Tian, C.; Jin, T.; Browning, K. L.; Sacci, R. L.; Veith, G. M.; Dai, S. (ACS Macro Lett., 2017)

(untitled) - Grätz, S.; Oltermann, M.; Troschke, E.; Paasch, S.; Krause, S.; Brunner, E.; Borchardt, L. (J. Mater. Chem. A, 2018)

(untitled) - Grätz, S.; Beyer, D.; Tkachova, V.; Hellmann, S.; Berger, R.; Feng, X.; Borchardt, L. (Chem. Commun., 2018)

(untitled) - Immohr, S.; Felderhoff, M.; Weidenthaler, C.; Schüth, F. (Angew. Chem., Int. Ed., 2013)

(untitled) - Dai, Y.; Zhang, X. (Polym. Chem., 2017)

(untitled) - Xu, J.; Feng, E.; Song, J. (J. Appl. Polym. Sci., 2014)

(untitled) - Feng, J.; Zhuo, R.-X.; Zhang, X.-Z. (Prog. Polym. Sci., 2012)

(untitled) - Kamber, N. E.; Jeong, W.; Waymouth, R. M.; Pratt, R. C.; Lohmeijer, B. G. G.; Hedrick, J. L. (Chem. Rev., 2007)

(untitled) - Sherck, N. J.; Kim, H. C.; Won, Y.-Y. (Macromolecules, 2016)

(untitled) - Nederberg, F.; Lohmeijer, B. G. G.; Leibfarth, F.; Pratt, R. C.; Choi, J.; Dove, A. P.; Waymouth, R. M.; Hedrick, J. L. (Biomacromolecules, 2007)

(untitled) - Lohmeijer, B. G. G.; Pratt, R. C.; Leibfarth, F.; Logan, J. W.; Long, D. A.; Dove, A. P.; Nederberg, F.; Choi, J.; Wade, C.; Waymouth, R. M.; Hedrick, J. L. (Macromolecules, 2006)

(untitled) - Andersen, J.; Mack, J. (Angew. Chem., Int. Ed., 2018)

(untitled) - Kulla, H.; Wilke, M.; Fischer, F.; Röllig, M.; Maierhofer, C.; Emmerling, F. (Chem. Commun., 2017)

(untitled) - Matsuo, J.; Aoki, K.; Sanda, F.; Endo, T. (Macromolecules, 1998)

(untitled) - Hutchings, B. P.; Crawford, D. E.; Gao, L.; Hu, P.; James, S. L. (Angew. Chem., Int. Ed., 2017)

(untitled) - Užarević, K.; Ferdelji, N.; Mrla, T.; Julien, P. A.; Halasz, B.; Friščić, T.; Halasz, I. (Chem. Sci., 2018)

(untitled) - Baral, E. R.; Lee, J. H.; Kim, J. G. (J. Org. Chem., 2018)